Pengaruh Penyuluhan Seks Pada Remaja Terhadap Pengetahuan Dan Sikap Tentang Perilaku Seks Bebas - Iis, Islamiyah; Noviyanti, Asri Dwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Free sex is a sexual relationship carried out by a man and a woman without a marriage bond. Efforts to prevent free sex are by getting closer to God Almighty, instilling moral and religious values from an early age, avoiding behaviors that will stimulate sexuality, and education. This study aims to determine the influence of sex education on adolescents on knowledge and attitudes about free sex behavior in SMA Negeri 5 Kendari. The type of research is quantitative with Pre Experimental using One Group Pretest-Posttest Design. Of the 432 populations, 81 samples were obtained through Simple Random Sampling that met the inclusion criteria. The analysis method uses the Wilcoxson test and the Mc-Nemar test. In the results of the Wilcoxson test, the value of knowledge and attitude was obtained, namely p = 0.000 or Ho was rejected and Ha was accepted, meaning that there was a significant influence before and after counseling was given, and in the results of the Mc Nemar test, the result was obtained that the two variables had the same influence with a value of p = 0.000. From the results of this study, it was concluded that there was an influence of sex counseling on adolescents on knowledge and attitudes about free sex behavior at SMA Negeri 5 Kendari. The results of this study are expected to increase knowledge about free sex behavior and try to find out the right and responsible information.